Kajian kalor reaksi tembaga sulfat (CuSO4.5H2O) melalui prototipe kalorimeter - Dian Herlinda Octorina Howan (Jurnal Kimia Fullerene, 2019)
Determination of dissolution heat reaction of copper sulfate hydrate, CuSO4.5H2O and copper sulfate anhydrous, CuSO4 using a calorimeter prototype was carried out. The initial stage is carried out by measuring the calorimeter constant and then measuring the heat of copper sulphate dissolution using Hess's Law to determine the heat of reaction indirectly. The results obtained by the dissolution reaction reaction of copper sulfate CuSO4.5H2O and copper sulfate anhydrous CuSO4 respectively were 723,318 J and 748,26 J.